A systematic review of factors influencing older adults' decision to accept or decline cancer treatment. Issue 2 (February 2015) - Puts, Martine T.E.; Tapscott, Brianne; Fitch, Margaret; Howell, Doris; Monette, Johanne; Wan-Chow-Wah, Doreen; Krzyzanowska, Monika; Leighl, Nathasha B.; Springall, Elena; Alibhai, Shabbir M.
Highlights Factors for accepting or declining treatment were similar. Convenience, treatment success rates and side effects were important factors. Many older patients just accepted the physician's treatment recommendation. Treatment experiences of others influenced the treatment decision.